Acute Effects of the French Contrast Method and Post Activation Potentiation on 3 × 3 Basketball Game Demands and Thermal Asymmetry Responses - Çağdaş Özgür Cengizel; Ömer Şenel (Applied Sciences)
This study aimed to determine the acute effects of the French contrast method (FCM) and post-activation potentiation (PAP) protocols on 3 × 3 basketball game demands and thermal asymmetry in male basketball players and to compare these effects between protocols. Eighteen male basketball players (mean ± SD; age: 21.7 ± 1.5 years, 10.6 ± 1.9 years of experience) visited the laboratory four times, 72 h apart. The players participated in three different protocols (baseline: 3 × 3 game; FCM + 3 × 3 game; PAP + 3 × 3 game; respectively). The players’ internal and external loads were monitored, game profiles were analyzed, and thermography was applied during the protocols. The results revealed that FCM and PAP did not significantly differ in internal load; however, the significant highest total distance and distance in band 2 during the 3 × 3 basketball game was after the FCM. The 1-point attempt was significantly higher after the FCM, and turnover was significantly higher after PAP. Significant thermal asymmetry was observed in the abdominals and lower back after the FCM and PAP. The results of this study provide coaches and practitioners with detailed information regarding the game demands that can be used to improve the playing profile of 3 × 3 basketball players.